Area of a Region

Calculus Level pending

Find the region bounded by the curve 9 x 2 6 x y + y 2 12 10 x 36 10 y = 0 {\bf 9x^2 - 6xy + y^2 - 12\sqrt{10}\:x - 36\sqrt{10}\:y = 0 } and the line 10 x 3 10 y + 30 = 0. {\bf -\sqrt{10}\:x - 3\sqrt{10}\:y + 30 = 0. }


The answer is 24.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Oct 15, 2016

Using the equations of rotation to rotate the x and y axis we have:

x = x c o s θ y s i n θ {\bf x = x' cos\theta - y' sin\theta }

y = x s i n θ + y c o s θ {\bf y = x' sin\theta + y' cos\theta }

Replacing the equations of rotation in the original equation and simplifying we obtain:

( 9 c o s 2 θ 6 c o s θ s i n θ + s i n 2 θ ) x 2 + 2 ( 4 s i n ( 2 θ ) + 3 c o s ( 2 θ ) ) x y + {\bf (9 cos^2\theta - 6 cos\theta sin\theta + sin^2\theta)x'^2 + -2(4 sin(2\theta) + 3 cos(2\theta))x'y' +}

( 9 s i n 2 θ + 6 c o s θ s i n θ + c o s 2 θ ) y 2 12 10 ( c o s θ + 3 s i n θ ) x + 12 10 ( s i n θ 3 c o s θ ) y = 0. {\bf (9 sin^2\theta + 6 cos\theta sin\theta + cos^2\theta)y'^2 - 12\sqrt{10}(cos\theta + 3 sin\theta)x' + 12\sqrt{10}(sin\theta - 3 cos\theta)y' = 0. }

To eliminate the x y {\bf x'y' } term set 4 s i n ( 2 θ ) + 3 c o s ( 2 θ ) = 0 t a n ( 2 θ ) = 3 4 {\bf 4 sin(2\theta) + 3 cos(2\theta) = 0 \implies tan(2\theta) = -\frac{3}{4} }

t a n 2 θ = 2 t a n θ 1 t a n 2 θ = 3 4 {\bf \implies tan2\theta = \frac{2 tan\theta}{1 - tan^2\theta} = -\frac{3}{4} \implies }

3 t a n 2 θ 8 t a n θ 3 = 0 t a n θ = 8 ± 10 6 {\bf 3 tan^2\theta - 8 tan\theta - 3 = 0 \implies tan\theta = \frac{8 \:\pm \:10}{6} }

Choosing the positive value of t a n θ t a n θ = 3 c o s θ = 1 10 {\bf tan\theta \implies tan\theta = 3 \implies cos\theta = \frac{1}{\sqrt{10}} } and s i n θ = 3 10 {\bf sin\theta = \frac{3}{\sqrt{10}} \implies }

x = 1 10 x 3 10 y {\bf x = \frac{1}{\sqrt{10}} x' - \frac{3}{\sqrt{10}} y'}

y = 3 10 x + 1 10 y {\bf y = \frac{3}{\sqrt{10}} x' + \frac{1}{\sqrt{10}} y' }

Replacing the equations of rotation in the original equation and simplifying we obtain:

9 10 ( x 2 6 x y + 9 y 2 ) 6 10 ( 3 x 2 8 x y 3 y 2 ) + 1 10 ( 9 y 2 + 6 x y + y 2 ) {\bf \frac{9}{10}(x'^2 - 6 x'y' + 9 y'^2) - \frac{6}{10}(3 x'2 - 8 x'y' - 3 y'2) + \frac{1}{10}(9 y'^2 + 6 x'y' + y'^2) }

12 ( x 3 y ) 36 ( 3 x + y ) = 0 {\bf - 12(x' - 3 y') - 36(3 x' + y') = 0 }

y 2 = 12 x {\bf \implies y'2 = 12 x' }

So we have a parabola in the x'y' system with focus ( 3 , 0 ) {\bf (3,0) } and directrix x = 3. {\bf x' = -3. }

10 x 3 10 y + 30 = 0 y = 1 3 x + 10 {\bf -\sqrt{10}\:x - 3\sqrt{10}\:y + 30 = 0 \implies y = -\frac{1}{\sqrt{3}}\:x + \sqrt{10} }

Two point on this line are ( 0 , 10 ) {\bf (0,\sqrt{10}) } and ( 3 10 , 0 ) {\bf (3\sqrt{10},0) }

Rotating the point ( 0 , 10 ) {\bf (0,\sqrt{10}) } we have:

0 = 1 10 x 3 10 y {\bf 0 = \frac{1}{\sqrt{10}} x' - \frac{3}{\sqrt{10}} y' }

10 = 3 10 x + 1 10 y ( x = 3 , y = 1 ) {\bf \sqrt{10} = \frac{3}{\sqrt{10}} x' + \frac{1}{\sqrt{10}} y' \implies (x' = 3,y' = 1) }

Similarily, rotating the point ( 3 10 , 0 ) ( x = 3 , y = 9 ) {\bf (3\sqrt{10},0) \implies (x' = 3,y' = -9) }

{\bf \therefore } In the x y {\bf x'y'} system we have the line x = 3 , {\bf x' = 3, \:} and the curve y 2 = 12 x {\bf y'^2 = 12 x' } and the line x = 3 {\bf x' = 3 } intersect at ( 3 , 6 ) {\bf (3,6) } and ( 3 , 6 ) {\bf (3,-6) \implies }

The area A = 6 6 3 y 2 12 d y = 3 y y 3 36 6 6 = 24. {\bf = \int_{-6}^{6} 3 - \frac{y'^2}{12} dy' = 3y' - \frac{y'^3}{36}|_{-6}^{6} = 24.}

Followed this link and exactly get the same results! Very monstrous computation, but very nice results at the end! Nice problem!

Michael Huang - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...